GEDUNG PERTUNJUKAN TEATER TAMAN BUDAYA BANJARBARU - Ariani, Bunga Suchie; Hartono, Rudi (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
The development of the Theater in South Kalimantan, especially Banjarbaru continues to grow rapidly. This is not appropriate with the lack of existing facilities and infrastructure makes theatre activities in South Kalimantan not well developed. Therefore in 2019, South Kalimantan Provincial Government together with Banjarmasin Cultural Park will plan the construction of Theatre Performance Building in a New Cultural Park Area which is located in the Governor’s Office Area of South Kalimantan. They want Theater Performance Building with an adequate lighting system and functional support space with directional access. Beside that, they want this Performance Building to become a Landmark in Banjarbaru City with the nuance of South Kalimantan Architecture. Therefore, the suitable method chosen is the Iconic Architectural Method which can be realized with 3 design principles based on a concept review, there are: (a) Traditional Elements, (b) Continuous Rhythm, and (c) Functional Elements. These three elements are realized by analyzing the point of view, circulation, material, color and texture of the interior and exterior in order to produce a good performance building design according to the client's needs.